Examining intersections between visual literacy and digital technologies in English language programs for higher education. Issue 4 (2nd October 2018) - Villamizar, Andres Gabriel
Abstract: Tertiary students from non-English speaking backgrounds are often required to undertake preparatory language courses. Whilst these programs help them achieve an operational level of academic English, their curricula do not explicitly promote the development of essential 21st century visual literacy skills. Understandings of visual literacy in adult English language teaching seem to overly simplify it as using images to complement written texts, generally through the use of technologies. This article examines intersections between classroom practices, visual literacy and the use of digital technologies in English language courses for higher education. Employing a case study methodology, the research comprised interviews with seven teachers in three university-based English language centres in Melbourne, Australia. Findings indicate that whilst these educators routinely access, select and share still and moving images through digital technologies, these practices are not aimed at honing their learners' visual literacy skills. Furthermore, pressure on teachers to achieve institution-driven objectives – which focus on reading, writing and speaking skills – limits students' opportunities for communication through visual texts. This article exposes limitations on research on the role of visual literacy in English language teaching, specifically in the higher education context, and argues the need for streamlined changes in curriculum and pedagogies.